Safe and Effective Treatment of Intracranial Infantile Hemangiomas with Beta-Blockers - Aoife Naughton; Ariel Yuhan Ong; Goran Darius Hildebrand (MDPI AG, 2021)
Infantile hemangiomas are common benign vascular tumors but are rarely found in an intracranial location. Our literature review identified 41 reported cases. There is no general consensus on management of these rare lesions and until recently, treatment was limited to surgery or pharmacological management with steroids or interferon. Although beta-blockers have been widely prescribed in the treatment of cutaneous infantile hemangiomas since 2008, their use in the treatment of intracranial infantile hemangiomas has been minimal. We present a case of infantile hemangioma affecting the right orbit, associated with intracranial extension, causing intermittent right facial nerve palsy. The patient achieved an excellent outcome following combined treatment with oral propranolol and topical timolol maleate 0.5%, with complete regression of the lesion by 4 months. We conclude that beta-blockers are a safe and effective treatment of intracranial infantile hemangiomas and can be employed as first-line management of these lesions.